Change They Can't Believe In : The Tea Party and Reactionary Politics in America - Updated Edition - Parker, Christoper S. (Book collections on Project MUSE., 2014)
Are Tea Party supporters merely a group of conservative citizens concerned about government spending? Or are they racists who refuse to accept Barack Obama as their president because he's not white? Change They Can't Believe In offers an alternative argument that the Tea Party is driven by the reemergence of a reactionary movement in American politics that is fueled by a fear that America has changed for the worse. Providing a range of original evidence and rich portraits of party sympathizers as well as activists, Christopher Parker and Matt Barreto show that what actually pushes Tea Party supporters is not simple ideology or racism, but fear that the country is being stolen from "real Americans", a belief triggered by Obama's election. From civil liberties and policy issues, to participation in the political process, the perception that America is in danger directly informs how Tea Party supporters think and act.